Data and Technology Based Bureaucratic Governance Innovations: A Model for Strengthening Institutional Quality in Public Sector Reform in Indonesia - Hermawan, Muhammad Distian Andi (Center for Maritime Policy Governance Studies (CMPGS), 2025)
This study aims to examine the role of data-driven governance innovation in improving institutional quality in the Indonesian public sector. Specifically, the research analyzes the direct and indirect effects of technology, organizational capacity, and regulatory frameworks on institutional quality, with data-driven governance innovation positioned as a mediating variable. The study responds to the growing demand for evidence-based public administration amid digital bureaucracy reform and the implementation of e-government initiatives in Indonesia. The research employs a mixed-methods approach with a sequential explanatory design. Quantitative data were collected through a structured survey of civil servants across central and local government institutions that have implemented digital governance systems. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to test measurement validity, reliability, and structural relationships among variables. This quantitative phase was complemented by qualitative data obtained from in-depth interviews with key informants involved in digital governance, which were analyzed thematically to provide contextual explanations of the statistical findings. The results indicate that data-driven governance innovation has a positive and significant effect on institutional quality. Technology emerges as the most influential factor, exerting both direct and indirect effects through governance innovation. Organizational capacity shows a moderate but significant influence, while regulatory factors display a weak and inconsistent effect. These findings suggest that strengthening technological infrastructure and organizational capabilities is essential for enhancing institutional quality through data-driven governance in the public sector.